Magnetic resonance imaging abnormalities of peripheral nerve and muscle are common in amyotrophic lateral sclerosis and share features with multifocal motor neuropathy. Issue 1 (28th May 2015) - Staff, Nathan P.; Amrami, Kimberly K.; Howe, Benjamin M.
ABSTRACT Introduction: Magnetic resonance imaging (MRI) of peripheral nerve and muscle in patients with amyotrophic lateral sclerosis (ALS) may be performed to investigate alternative diagnoses, including multifocal motor neuropathy (MMN). MRI findings of peripheral nerve and muscle are not well described in these conditions, making interpretation of results difficult. Methods: We examined systematically the peripheral nerve and muscle MRI findings in patients with ALS (n = 60) and MMN (n = 8). Results: In patients with ALS and MMN, abnormal MRIs were common (85% and 75%, respectively), but did not correlate with disease severity. Peripheral nerve MRI abnormalities were similar in frequency (ALS 58%, MMN 63%), with most changes being of mild to moderate severity. Muscle MRI changes were more common in ALS (57% vs. 33%), and no muscle atrophy was seen in patients with MMN. Conclusion: MRI abnormalities of peripheral nerve and muscle in ALS and MMN are common and share some features. Muscle Nerve52: 137–139, 2015